Tren Publikasi Ilmiah tentang Muhammadiyah Periode 2014–2024: Analisis Bibliometrik Berbasis Scopus Menggunakan VOSviewer - Rizky Hidayanto; Fajar Junaedi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
This study aims to map the development of Scopus-indexed scientific publications on Muhammadiyah during the 2014–2024 period using bibliometric analysis assisted by VOSviewer. Data were retrieved from the Scopus database using the keyword Muhammadiyah in the title, abstract, and keywords fields. Document selection followed the PRISMA 2020 guidelines, resulting in 676 articles eligible for analysis. The analysis examined publication trends, source journals, authors, institutional affiliations, contributing countries, and keyword mapping through network, overlay, and density visualizations. The findings reveal a substantial increase in Muhammadiyah-related publications over the past decade, with the highest productivity recorded in 2020. Research on Muhammadiyah has expanded into multidisciplinary domains through contributions from diverse journals, authors, institutions, and countries. Keyword co-occurrence analysis identified 223 items grouped into three major clusters covering organizational and Islamic studies, empirical health-related research, and education. Overlay visualization indicates a shift from education-oriented topics toward organizational, policy, health, and contemporary social issues, while density visualization highlights the most intensively studied themes. These findings demonstrate that scientific publications on Muhammadiyah has become increasingly broad and multidisciplinary, while also identifying opportunities for future research on emerging and underexplored topics.